A Visual Deconstruction of La Salaga: Unveiling the Traditional Visual Language in A Balinese Painting by I Made Sesangka Puja Laksana - Aditia Gilang Romadhon, Mohammad; Laksani, Hening; Herry Prilosadoso, Basnendar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This research aimed to explore wimba (image), wimba methods, and expressions in the “La Salaga” painting by I Made Sesangka Puja Laksana with a focus on the structure of the storyline. This research used a descriptive qualitative research method, where the data collection technique focused on the analysis of visual language from the painting. The visual analysis included exploring the meanings of Balinese and Sulawesi culture based on how wimba created the visual narrative and visual construction in the painting. The results of this study concluded that the content of wimba or image, the method used to depict the image, and the meaning of the painting in La Salaga by I Made Sesangka Puja Laksana contained the storyline of the painting that expresses a particular space.